Can hematological parameters in type 2 diabetes predict microvascular complication development? - Onalan, Erhan; Gozel, Nevzat; Donder, Emir (Professional Medical Publications, 2019)
Objective: To examine potential associations between neutrophil/lymphocyte ratio, platelet/lymphocyte ratio, mean platelet volume (MPV), HbA1c and microvascular complications in diabetic patients from a cost-effectiveness perspective. Methods: One hundred patients with type 2 diabetes attending our outpatient unit between May 2018 and October 2018 were included, and 100 healthy individuals served as the control group. A retrospective file search was performed to collect information on hemoglobin, mean platelet volume (MPV), glycosylated haemoglobin (HbA1c), hematocrit (Hct), neutrophil and lymphocyte count, neutrophil/lymphocyte ratio (NLR), platelets (Plt), platelet/lymphocyte ratio (PLR), and microvascular complications (neuropathy, retinopathy, nephropathy). Results: Demographic and laboratory data were retrospectively controlled between diabetes (n=100) and healthy control (n=100) groups. The mean age in diabetic patients and healthy controls was 56.34 and 36.68 years, respectively. The mean NLR in diabetics and healthy controls was 2.48 and 2.11, the difference in NLR being significant (p=0.002). MPV in diabetics and controls was 8.54 and 8.53, respectively, and the difference was not significant (p=0.93). PLR was also similar, i.e. 149.7 and 145.3 in diabetics and healthy controls (p=0.067). With respect to microvascular complications, retinopathy was found to be significantly associated with MPV and NLR (p=0.015, and p=0.051), and nephropathy showed a significant association with NLR (p=0.027) among diabetics. In contrast with the two other microvascular complications, no significant association between neuropathy and NLR could be detected, while PLR and neuropathy was significantly associated (p=0.003). Conclusion: Microvascular complications may be associated with certain hematologic parameters, as suggested by comparisons both between diabetics and healthy individuals and within the group of diabetic individuals. We believe that hematologic parameters such as hematocrit, MPV, NLR, and PLR, which can be obtained through a simple complete blood count, may be utilized as cost-effective predictors of diabetic microvascular complications. Further prospective studies with larger sample size are required to better delineate these associations.
Keywords: Diabetes mellitus; Neutrophil/lymphocyte ratio; Platelet/lymphocyte ratio; Haemoglobin A1c